The Influence of Parental Attention, Student Habits and Academic Achievement on Learning Outcomes through Student Learning Motivation - Dwi Aryati; Indri Fitriyanti Gustian (Jurnal Sinar Edukasi, 2022)
This research aims to analyze the influence of parental attention, student habits, and academic achievement on learning outcomes through student learning motivation in Jambi Province. The research method used was a quantitative approach with survey techniques, involving high school students as respondents. Data was collected through a questionnaire designed to measure the variables of parental attention, student habits, academic achievement, learning motivation and learning outcomes. The results of data analysis show that parental attention, student habits, and academic achievement have a positive and significant influence on student learning motivation. Apart from that, student learning motivation has also been proven to have a positive and significant influence on learning outcomes. Path analysis shows that student learning motivation mediates the influence of parental attention, student habits, and academic achievement on learning outcomes. The findings of this research emphasize the important role of parental attention and good study habits in increasing students' learning motivation, which in turn has a positive impact on their learning outcomes. Therefore, it is recommended that parents become more involved in their children's educational process and that schools develop programs that can improve students' learning habits as well as their academic achievements.